Relationship Resonances in the Learning Process as Found in Stevenson's Kidnapped and the Cherokee Story, The Gambler - Rockey Robbins; Sharla Robbins; Wiley Harwell (University of Oklahoma Libraries, 2020)
In a time of racial division, this critical study explores both the history and possibility of reconciliation of, not only the complicated relationship between the Scottish and Cherokee peoples, but also within an analysis of, two stories: Kidnapped by Robert Louis Stevenson and the traditional Cherokee story, The Gambler. Using Object Relations Theory, along with the concept of Resonance, readers will find connections between the main characters, David Balfour and Cooch, as well as implications further analysis and the relationships teachers may establish in the classroom.